High thermoelectric performance through crystal symmetry enhancement in triply doped diamondoid compound Cu₂SnSe₃ - Hu, Lei (2022)
The presence of high crystallographic symmetry and nanoscale defects are favorable for thermoelectrics. With proper electronic structures, a highly symmetric crystal tends to possess multiple carrier channels and promote electrical conductivity without sacrificing Seebeck coefficient. In addition, nanoscale defects can effectively scatter acoustic phonons to suppress thermal conductivity. Here, it is reported that the triple doping of Cu2SnSe3 leads to a high ZT value of 1.6 at 823 K for Cu1.85Ag0.15(Sn0.88Ga0.1Na0.02)Se3, and a decent average ZT (ZTave) value of 0.7 is also achieved for Cu1.85Ag0.15(Sn0.93Mg0.06Na0.01)Se3 from 475 to 823 K. This study reveals: 1) Ag doping on Cu sites generates numerous point defects and greatly decreases lattice thermal conductivity. 2) Doping Mg or Ga converts the monoclinic Cu2SnSe3 into a cubic structure. This symmetry enhancing leads to an increase in the effective mass from 0.8 me to 2.6 me (me, free electron mass) and the power factor from 4.3 µW cm−1 K−2 for Cu2SnSe3 to 11.6 µW cm−1 K−2. 3) Na doping creates dense dislocation arrays and nanoprecipitates, which strengthens the phonon scattering. 4) Pair distribution function analysis shows localized symmetry breakdown in the cubic Cu1.85Ag0.15(Sn0.88Ga0.1Na0.02)Se3. This work provides a standpoint to design promising thermoelectric materials by synergistically manipulating crystal symmetry and nanoscale defects.